Penggunaan NaCL dan Asam Sitrat untuk Memperpanjang Umur Simpan dan Mutu Cabai Rawit (Capsicum frutescens L.) - St. Sabahannur (JURNAL GALUNG TROPIKA, 2020)
Chili cannot be stored for a long time in a fresh condition because it was a living structure that is still carrying out metabolic reactions. Chili after harvesting still maintains the physiological system as it was still attached to the plant. Metabolic reactions will trigger chili damage quickly. The efforts to prevent this should be made to maintain the quality and shelf life of chilies by minimizing metabolic processes, such as suppressing the rate of respiration through regulating the environmental conditions of storage and use of preservatives. The study aimed to determine the effect of concentration of NaCl and citric acid on the shelf life and quality of chili. The study was arranged using a Completely Randomized Design (CRD) with a combination of types and concentrations of preservatives. with the treatment of NaCl concentrations of 1%, 2%, 3%, and Citric Acid respectively 1%, 2%, 3%. The parameters observed were weight loss, shelf life, texture, total microbes, and vitamin C content. The results showed that the use of preservatives significantly affected the shelf life and quality of cayenne pepper. The preservative NaCl 3% given a better effect on cayenne pepper, in terms of the lowest weight loss of 22.8%, the maximum shelf life of 78 days, the number of microbes 12 cfu/g sample, and the texture is rather soft after storage.